“Inside His Idiom:” E. M. Forster’s T. S. Eliot - Jason FINCH (E-REA)
Counter to previous assumptions, relations between E.M. Forster and T.S. Eliot are important to an understanding of the work of each, and reshape our view of their period. These mutual influence relations also enable revised theories of literary influence to be proposed. The two writers shared privileged upbringings founded on nineteenth-century capitalism. The friendship of each with Virginia Woolf brought them into contact with one another and then, in the 1920s, they were linked by The Criterion, which Eliot edited. The article examines two pieces of prose by Forster on Eliot, one gathered into his first collection of essays, Abinger Harvest (1936) and the other into Two Cheers for Democracy (1951). Over time, Forster came to see Eliot as self-deceiving and harmed by his attachment to conservative Christianity. If Eliot drew on Forster’s work it was early in his career, before The Waste Land. Forster and Eliot can be understood in social terms as mandarins of British culture in the mid-twentieth century. While Eliot seemed to pay little attention to Forster in later years, Forster’s career can be read as shadowed by Eliot’s.